2015
DOI: 10.1520/jte20140094
|View full text |Cite
|
Sign up to set email alerts
|

Improving Corporate Governance Effects on an Enterprise Crisis Based on a New Hybrid DEMATEL with the MADM Model

Abstract: The purpose of this study is to set up a new enterprise crisis improvement model for corporate governance based on the hybrid MADM model, which addresses on the main causal factors and amended priorities in order to reduce the occurrence of corporate crises. In this study, we present the use of a new hybrid MADM combined with a DEMATEL technique to construct an influential network relationship map (INRM) and find the influential weights of DANP in criteria from the influential relationship matrix, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…To overcome this challenge, we employ FS to determine the most important features without deteriorating the model's forecasting quality [77][78][79][80]. However, none of the specific FS techniques can reach the best performance under all assessment measures.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this challenge, we employ FS to determine the most important features without deteriorating the model's forecasting quality [77][78][79][80]. However, none of the specific FS techniques can reach the best performance under all assessment measures.…”
Section: Discussionmentioning
confidence: 99%
“…The global weights can also be obtained using the influence relation matrix through these hybrid methods [28]. Because the influence level is a characteristic of the weights, this study referred to these as the IWs of DANP [28][29][30][31][32][33][92][93][94][95]. The modified VIKOR method was then used to calculate the ratio of the gap between the real performance f kj and the aspiration level f aspired j in the alternative k pk " 1, 2, ..., Kq of criterion j pj " 1, 2, ..., nq; that is r kj " p| f aspired j´f kj |q{p| f aspired j´f worst j |q such that the calculations of the IWs are integrated among various programs.…”
Section: Method: Danp-v Modelmentioning
confidence: 99%
“…Therefore, we use a new hybrid MADM model developed for improving China's regional financial center modernization. We adopt the DEMATEL technique through expert knowledge and practical experience to establish an influence relation matrix for constructing an influential network relation matrix (INRM) and determining the IWs of the DANP, which is based on the ANP concept [103,104], to solve practical problems [32,33,92]. Hence, the calculation of the IWs of the DANP involves the following steps as:…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This method is used as the basic concept of the TOPSIS method (Hwang, Yoon 1981) on Euclidean distances to the positive ideal (this research adopts the aspiration level) and the negative ideal (this research adopts the worst level) solutions, and TOPSIS used the class Euclidean distance function (Yu 1973), as based the concept of the positive ideal and negative ideal solutions; then Opricovic and Tzeng (2004) found that the TOPSIS method cannot be used in ranking or selection, and proposed the VIKOR method to replace the TOPSIS method, by comparing the preference distance of all real alternatives in order to stay close to the positive-ideal point; however, this research adopted the basic idea of the traditional thinking of the VIKOR method to replace staying close to the aspiration level (Liu et al 2012;Chen 2015;Hu et al 2015). The gap concept measures the proximity to the positive ideal point in order to modify the aspiration level point.…”
Section: Modified Vikor Methodsmentioning
confidence: 99%
“…These basic concepts were used to create a series of new hybrid MADM models for solving complex and dynamic real world problems (Peng, Tzeng 2013;Tzeng, Huang 2012;Lu et al 2013Lu et al , 2015Hu et al 2015;Chen, Chi 2015;Liou et al 2014Liou et al , 2016. The DEMATEL technique involves three steps, detailed as follows.…”
Section: Dematel Techniquementioning
confidence: 99%